Myositis induced by durvalumab in a patient with non‐small cell lung cancer: A case report. Issue 12 (26th October 2020) - Kobayashi, Miyuki; Saiki, Masafumi; Omori, Chisa; Ide, Shuichiro; Masuda, Kazuki; Sogami, Yusuke; Hata, Takanori; Ishihara, Hiroshi
Abstract : Immune checkpoint inhibition is associated with a broad spectrum of immune toxicities referred to as immune‐related adverse events (irAEs). Myositis is known to be a potentially fatal irAE. Here, we report a case of immune‐related myositis after the administration of durvalumab. A 60‐year‐old man with stage IIIA lung adenocarcinoma was treated with durvalumab after concurrent chemoradiation therapy. After the third dose of durvalumab, his serum CK level was elevated, and soon thereafter myalgia of the proximal muscles and blepharoptosis were observed. We diagnosed immune‐related myositis based on the results of pathological examination and initiated systemic corticosteroid therapy. His symptoms then improved and the serum CK level immediately dropped to within a normal range. Clinicians should be aware of possible myositis during the early phase of durvalumab therapy. Abstract : We report a case of immune‐related myositis after administration of durvalumab in patient with non‐small cell lung cancer (NSCLC).